THEORETICAL AND BASIC ISSUES OF ORGANIZING INTERNATIONAL FESTIVALS - Nurullayeva Zarina (International Journal of Literature and Language Studies, 2026)
This text describes the socio-cultural nature of festivals, their global and national importance, and the role of Uzbekistan's international festivals in promoting the national heritage. In addition to world-famous holidays, the article analyzes the organizational and financial mechanisms and artistic features of the